(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This article explores the methods of using modern technologies to teach foreign languages in elementary grades. It discusses how tools such as language learning apps, gamification, multimedia resources, and virtual exchanges can enhance language acquisition. The article highlights the benefits of increased engagement, personalized learning, and accessibility. Additionally, examines the challenges of technology integration, including the digital divide and need for teacher training. The conclusion offers pedagogical recommendations for successfully incorporating technology into foreign language instruction.